<h3>
<u>Explanation</u></h3>
We have the given slope value and the coordinate point that the graph passes through.
![y = mx + b](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20b)
where m = slope and b = y-intercept. Substitute the value of slope in the equation.
![y = - \frac{3}{4} x + b](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%20b)
We have the given coordinate point as well. After we substitute the slope, we substitute the coordinate point value in the equation.
![3 = - \frac{3}{4} (4) + b \\](https://tex.z-dn.net/?f=3%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20%284%29%20%2B%20b%20%5C%5C%20)
<u>Solve</u><u> </u><u>the</u><u> </u><u>equation</u><u> </u><u>for</u><u> </u><u>b-term</u>
![3 = - 3 + b \\ 3 + 3 = b \\ 6 = b](https://tex.z-dn.net/?f=3%20%3D%20%20-%203%20%2B%20b%20%5C%5C%203%20%2B%203%20%3D%20b%20%5C%5C%206%20%3D%20b)
The value of b is 6. We substitute the value of b in the equation.
![y = - \frac{3}{4} x + 6](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%206)
We can also use the Point-Slope form to solve the question.
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
Given the y1 and x1 = the coordinate point value.
Substitute the slope and coordinate point value in the point slope form.
![y - 3 = - \frac{3}{4} (x - 4)](https://tex.z-dn.net/?f=y%20-%203%20%3D%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20%28x%20-%204%29)
<u>Simplify</u><u>/</u><u>Convert</u><u> </u><u>into</u><u> </u><u>Slope-intercept</u>
![y = - \frac{3}{4} (x - 4) + 3 \\ y = - \frac{3}{4} x + \frac{12}{4} + 3 \\ y = - \frac{3}{4} x + 3 + 3 \\y = - \frac{3}{4} x + 6](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20%28x%20-%204%29%20%2B%203%20%5C%5C%20y%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%20%20%5Cfrac%7B12%7D%7B4%7D%20%20%2B%203%20%5C%5C%20y%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%203%20%2B%203%20%5C%5Cy%20%3D%20%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%206)
<h3>
<u>Answer</u></h3>
<u>
</u>
Answer:
-u+5
Step-by-step explanation:
plz mark as brainliest
Answer:
x≈ 3.2056
Step-by-step explanation:
Set both sides by log. Then, solve for x.
1. 14^(x + 1) = 36
(x + 1)log(14) = log(36)
x + 1 = log(36)/log(14) . . . Divide both sides by log(14)
x = log(36)/log(14) - 1 . . . . Subtract both sides by 1.
x ≈ 0.3579 . . . . . . . . . . . .Use calculator to simplify the expression.
Note that the second problem is similar to the first.
2. 12^(y - 2) = 20
(y - 2)log(12) = log(20)
y - 2 = log(20)/log(12)
y = log(20)/log(12) + 2
y ≈ 3.2056